Design of PID Controller Module Using PLC On 3 Phase Motor - Kartika, Vinda Setya; Sayekti, Ilham; Pramuji, Tulus; Rizal, Aminuddin; Handoko, Slamet (JAICT, 2025)
Proportional Integral Derivative (PID) is a control system that combines proportional, integral, and derivative elements. PID control is often used in industrial machines. One of these machines is a 3-phase motor. Another important component in the industrial world is the Programmable Logic Controller (PLC) which is usually paired with an interface tool, namely HMI. The importance of a deep understanding of PID, PLC, HMI, and 3-phase motors is very important for students to be better prepared to face the real world of work. The application of the PID controller module using PLC as a learning tool at the Semarang State Polytechnic is still lacking, one of the reasons being the availability of PID controller modules that are inadequate. This study aims to design a PID controller module using PLC on a 3-phase motor. The creation of this practical module uses Omron HMI as a monitor in controlling 3-phase motor movements. Push buttons and switches are used as input components. Omron CP1E PLC is used as a processing component according to motor movement. The encoder is used to read the motor speed with an output in the form of a square signal which will be the feedback input read by the PLC. The inverter is used as a 3-phase induction motor driver. Buzzer and lights are used as indicators in controlling 3-phase motors. 3-phase induction motors are the main output components in this PID system. The power supply is used as a voltage source for the PLC so that the power supply must always be connected to a 220 VAC source. MCB is used as a protection system on the module.